(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
Turmeric is a popular spice that is cultivated all across the Indian subcontinent. Traditional medicine has utilized turmeric as a treatment for a variety of ailments, including cough, diabetes, and hepatic problems. Turmeric and its derivatives have been studied extensively over the past several decades to determine their pharmacological properties. Turmeric’s primary chemical component, curcumin, has been shown to have pro, antioxidant, anti - mutagenic, anti-diabetic, antimicrobial, cardio-protective, expectorant, and anticancer properties. This study focuses on the pharmacological effects of Turmeric, as well as its extracts and potential therapeutic applications, as well as their safety assessment. Since the dawn of time, man has used herbal products to treat illnesses. The Indian subcontinent has a diverse flora, including both fragrant and medicinal species. In the Indian traditional medicinal, this vast flora has been extensively used as a source of numerous medicines.